Upaya Penyadaran Pecandu Narkoba Melalui Nilai Religiusitas di Panti Rehabilitasi Pondok Tetirah Dzikir Yogyakarta - Ridho, Muhammad Rasyid; Tumin, Tumin (Jurnal Studi Islam dan Kemuhammadiyahan (JASIKA), 2023)
This study entitled efforts to awareness of drug addicts through the value of religiosity in pondok tetirah dhikr Rehabilitation Center yogyakarta. The purpose of this study is to determine the role of religiosity in the rehabilitation of drug addicts, efforts made in regaining awareness of drug addicts, and to determine the inhibiting factors in regaining awareness of drug addicts. This study uses a qualitative approach using descriptive analysis, while the data collection techniques used observation, interviews, and documentation. Data were analyzed using data reduction methods, data presentation, and drawing conclusions or verification. The research result of this undergraduate thesis writing is that, in implementing the role of religiosity as an effort to rehabilitate, Pondok Tetirah Dzikir refers to regain awareness using the Inabah method or better known in the Tarekat Qadiriyah Naqsabandiyah (TQN). Apart from that, Pondok Tetirah Dzikir, in the implementation of its activities, in the form of a rehabilitation program, the students are taught and accustomed to discipline in worship, activity, and is qualified in the social field. The model used in Pondok Tetirah Dzikir rehabilitation center in coaching drug abusers is by carrying out Islamic methods, such as prayer, dzikir (remembering God), repentance bathing, and another coaching that can support the rehabilitation process. In addition, in implementing the program, there are several inhibiting factors, such as inadequate facilities and infrastructure, lack of support from the parents of students, and minimal government attention.